Assessment of treatment patterns associated with injectable disease-modifying therapy among relapsing–remitting multiple sclerosis patients. Issue 1 (March 2017) - Nicholas, J; Ko, JJ; Park, Y; Navaratnam, P; Friedman, HS; Ernst, FR; Herrera, V
Background: Availability of oral disease-modifying therapy (DMT) for relapsing–remitting multiple sclerosis (RRMS) may affect injectable DMT (iDMT) treatment patterns. Objective: The objective of this paper is to evaluate iDMT persistency, reasons for persistency lapses, and outcomes among newly diagnosed RRMS patients. Methods: Medical records of 300 RRMS patients initiated on iDMT between 2008 and 2013 were abstracted from 18 US-based neurology clinics. Eligible patients had ≥3 visits: pre-iDMT initiation, iDMT initiation (index), and ≥1 visit within 24 months post-index. MS-related symptoms, relapses, iDMT treatment patterns (i.e. persistency, discontinuation, switching, and restart), and reasons for non-persistency were tracked for 24 months. Results: At 24 months, iDMT persistency was 61.0%; 28.0% of patients switched to another DMT, 8.0% discontinued, and 3.0% stopped and restarted the same iDMT. The most commonly identified reasons for non-persistency were perceived lack of efficacy (22.2%), adverse events (18.8%), and fear of needles/self-injecting (9.4%). At 24 months, 38.0% of patients had experienced a relapse and 11.0% had changes in MRI lesion counts. Patients without MS-related symptoms at index reported increases in the incidence of these symptoms at 24 months. Conclusions: Non-persistency with iDMT remains an issue in the oral DMT age. Many patients still experienced relapses and disease progression, and should consider switching to more effective therapies.